2003
DOI: 10.1002/jcla.10070
|View full text |Cite
|
Sign up to set email alerts
|

Reticulocyte parameters and hemoglobin F production in sickle cell disease patients undergoing hydroxyurea therapy

Abstract: Hemoglobin F (HbF) is an effective inhibitor of HbS polymerization. Hydroxyurea (HU) is used to increase HbF synthesis and improve the clinical course of sickle cell disease (SCD) patients. We studied a series of laboratory parameters concerning HbF production and reticulocyte response, and compared data between two groups: 1) 13 SCD patients treated with HU, and 2) 33 untreated SCD patients. Higher values of Hb concentration, mean cell volume (MCV), mean cell hemoglobin (MCH), mean reticulocyte volume (MRV), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
8
12
0
Order By: Relevance
“…In our study of a Brazilian population we detected a statistical correlation between HbF levels and PCV values, agreeing with the findings of a Nigerian study carried out by Falusi and Kulozik (1990). Borba et al (2003) found no association between the levels of HbF and Hb in Brazilians with SCA who were undergoing treatment with hydroxyurea, although their study did indicate a significant correlation between MCV and HbF levels. Buchanan et al (2004) suggested an association between high HbF levels and a low frequency of leg ulcers, supporting our observation that in our group of Brazilians outpatients with high HbF values had milder SCA phenotypic characteristics and needed fewer sessions of erythrocyte transfusions.…”
Section: Discussionsupporting
confidence: 91%
“…In our study of a Brazilian population we detected a statistical correlation between HbF levels and PCV values, agreeing with the findings of a Nigerian study carried out by Falusi and Kulozik (1990). Borba et al (2003) found no association between the levels of HbF and Hb in Brazilians with SCA who were undergoing treatment with hydroxyurea, although their study did indicate a significant correlation between MCV and HbF levels. Buchanan et al (2004) suggested an association between high HbF levels and a low frequency of leg ulcers, supporting our observation that in our group of Brazilians outpatients with high HbF values had milder SCA phenotypic characteristics and needed fewer sessions of erythrocyte transfusions.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, patients treated with HU presented increased MCV, MCH, total leukocyte count, and a significant decrease in platelet count compared to untreated patients. Permanence of high MCV, even after the use of HU, was also observed in sickle-cell patients using HU in previous studies (3,17,22) . The HU has also been associated with a decrease in platelet count, total leukocyte reduction and MCH, however, only the first result was observed in our study (5,6,20) .…”
Section: Discussionsupporting
confidence: 64%
“…(17) The MCV of patients in this study after starting treatment with HU increased significantly compared to before treatment. Thus, as there was a significant correlation between MCV and Hb F, it can be stated that in this study the increased Hb F is directly related to the increase of cell volume.…”
Section: Discussionmentioning
confidence: 68%